Práticas de leitura e de escrita: o cordel no ensino fundamental - Cunha, Angelita Gomes Fontenele Rodrigues da (Universidade Federal do Tocantins, 2020)
The present study “Reading and writing practices: cordel in elementary school” discusses cordel writing and reading practices, in an 8th grade class at a public school located in the countryside, in the city of Teresina, in the State of Piauí - PI. This work has as main objective to effect the literary literacy of the students. We emphasize that we chose to work with cord in the classroom in order to foster a closer relationship between students and literature. In addition, we consider the choice of our research object the region in which we live, as the cordel scene is very present and active. Methodologically, we use the steps of the didactic sequence proposed by Rildo Cosson (2018), seeking to adapt them to our reality and our teaching practices. As a theoretical basis we used the following authors, namely: Barros (2015), Bakhtin (1998, 2011, 2019), Barthes (2008), Burke (2010), Candido (2011, 2017), Vigotski (2010), Zumthor (1993, 2005, 2010, 2014) and Cascudo (1984). The research ia grounded on the studies of Barros (2015), Galvão (2002), Marinho and Pinheiro (2012), Pinheiro (2018), Zilberman (1988), Soares (1999), Testa (2015, 118, 2019), Cosson (2018), Ferreira (2014), Carvalho (2004), Clementino Neto (2010, 2011, 2016, 2018, 2019), Fontenele (2019), Lima (2016), Mendes Sobrinho (2006, 2010, 2018, 2019), Vieira (1980, 2020). As a result, we can highlight that students who commonly have difficulties with literary reading and with the production of poetic texts ended up effectively integrating themselves with string readings and with string productions (performed in the classroom). Thus, we verify how much the literature is able to “hook” the young students, mainly due to the issues of orality, language (sometimes less formal) and the themes (which strongly implied the memory and experiences of the cordelistas in this region). Therefore, cordel literature triggered an affective engagement of young students, in a special way, by valuing what students have of them